2023
DOI: 10.3389/fendo.2023.1144747
|View full text |Cite
|
Sign up to set email alerts
|

Studies related to osteosarcoma and metabolism from 1990 to 2022: A visual analysis and bibliometric study

Abstract: BackgroundOsteosarcoma is the most common primary bone tumor, its high incidence of metastasis and poor prognosis have led to a great deal of concern for osteosarcoma. In many cancer types, metabolic processes are important for tumor growth progression, so interfering with the metabolic processes of osteosarcoma may be a therapeutic option to stall osteosarcoma progression. A key mechanism of how metabolic processes contribute to the growth and survival of various cancers, including osteosarcoma, is their abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Finally, from 2013 to 2023, we analyzed emerging vocabulary in the NSCLC-Met field. CiteSpace is highly advantageous as it can display sudden terminology bursts in a particular research field during a specific time period to potentially reflect hotspots and trends ( 23 ). Keywords appearing in earlier periods indicated that scientists were focusing on the field at earlier stages, while more current keywords indicated the topic had suddenly attracted attention ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, from 2013 to 2023, we analyzed emerging vocabulary in the NSCLC-Met field. CiteSpace is highly advantageous as it can display sudden terminology bursts in a particular research field during a specific time period to potentially reflect hotspots and trends ( 23 ). Keywords appearing in earlier periods indicated that scientists were focusing on the field at earlier stages, while more current keywords indicated the topic had suddenly attracted attention ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…The dual-map overlay visually represents the paths of academic journal distribution, elucidating the exploration of OSA from foundational research to its translation into clinical, nursing, and medical studies. Key contributors to OSA research include Wang Y, Zhang Y, Gorlick R, Ferrari S, and Wang J, who form the backbone of OSA studies [ [26] , [27] , [28] ]. Notably, researchers from China, affiliated with esteemed institutions like Shanghai Jiao Tong University, have made substantial contributions.…”
Section: Discussionmentioning
confidence: 99%
“…Authors Bacci G and Bielack SS have over 1500 co-citations, underscoring their importance. In the author co-citation network, Mirabello L, Bacci G, and Bielack SS are prominent, establishing strong connections with other top-cited authors, solidifying their influence in OSA research [ [26] , [27] , [28] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microenvironment of OS is primarily hypoxic and acidic. Tumor cells predominantly depend on aerobic glycolysis and fatty acid metabolism to meet their energy demands, a metabolic strategy shared by highly efficient effector T cells [ 28 ]. Consequently, the competition for glucose as well as other fuel sources, such as fatty acids and oxygen, may detrimentally affect the proliferation and activation of effector T cells, culminating in a state of exhaustion within the TIME.…”
Section: Discussionmentioning
confidence: 99%